Simultaneous Single-/Dual- And Quad-Pol SAR Imaging over Swaths of Different Widths - Villan, Michelangelo; Krieger, Gerhard; Steinbrecher, Ulrich; Moreira, Alberto (IEEE Transactions on Geoscience and Remote Sensing, 2020)
Synthetic aperture radar (SAR) concepts based on digital beamforming (DBF) in elevation and multiple receive beams, for example, staggered SAR, allow high-resolution imaging of wide swaths and are, therefore, well-suited for the systematic observation of dynamic processes on the Earth's surface. While these concepts are compatible with quad-polarimetric (quad-pol) operation, due to severe ambiguity constraints, the achievable swath in the quad-pol mode is narrower than in the single- (or dual-) pol mode. Therefore, either the single- (or dual-) pol data over a wider swath or the quad-pol data over a narrower swath can be acquired. This article proposes a novel SAR acquisition mode, based on pulse-to-pulse alternation of the antenna pattern on transmit, which delivers at the same time single- (or dual-) pol data over a wider swath and quad-pol data over a narrower swath at the expense of an acceptable degradation of the ambiguity performance. This technique yields remarkable benefits for the design and operation of future SAR systems and represents an effective solution to manage and resolve conflicting user requirements.
Created from Fastlane, Scopus look-up
Keywords: Ambiguities; digital beamforming (DBF); dual-polarimetric (dual-pol) synthetic aperture radar (SAR); high-resolution wide-swath (HRWS) imaging; quad-polarimetric SAR; SAR; staggered SAR; Tandem-L